Association between Caffeine Consumption in Pregnancy and Low Birth Weight and Preterm Birth in the birth Cohort of Ribeirão Preto - Vitti, Fernanda Pino; Grandi, Carlos; Cavalli, Ricardo de Carvalho; Simões, Vanda Maria Ferreira; Batista, Rosângela Fernandes Lucena; Cardoso, Viviane Cunha (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To describe caffeine consumption during pregnancy and its association with low birth weight (LBW) and preterm birth in the birth cohort of Ribeirão Preto, state of São Paulo, Brazil, in 2010.Methods Cohort study, with descriptive and analytical approach. Data included 7,607 women and their newborns in Ribeirão Preto, state of São Paulo, Brazil. The women answered standardized questionnaires about reproductive health, prenatal care, life habits, sociodemographic conditions, and information about coffee intake. The independent variable was high caffeine consumption (≥300 mg/day) from coffee during pregnancy, and the dependent variables were LBW (birth weight < 2,500 g) and preterm birth (< 37 weeks of gestational age). Four adjusted polytomous logistic regression models, relative risk (RR) and 95% confidence interval (CI) were fitted: biological and sociodemographic conditions; obstetric history; current gestational conditions; and all variables included in the previous models.Results A total of 4,908 (64.5%) mothers consumed caffeine, 143 (2.9%) of whom reported high consumption. High caffeine intake was significantly associated with reduced education and with the occupation of the head of the family, nonwhite skin color, not having a partner, higher parity, previous abortion and preterm birth, urinary tract infection, threatened abortion, alcohol consumption and smoking. No association was found between high caffeine consumption and LBW or preterm birth in both unadjusted (RR = 1.45; 95% CI: 0.91–2.32; and RR = 1.16; 95% CI: 0.77–1.75, respectively) and adjusted analyses (RR = 1.42; 95% CI: 0.85–2.38; and RR = 1.03; 95% CI: 0.65–1.63, respectively).Conclusion In this cohort, high caffeine intake was lower than in other studies and no association with LBW or preterm birth was found.
Keywords: caffeine; pregnancy; cohort studies; low birth weight; preterm birth